Religion and social change in modern Turkey : the case of Bediüzzaman Said Nursi - Mardin, Şerif (Albany : State University of New York Press, 1989)
Annotation Mardin (public administration, Bogazigi University, Istanbul) uses the example of the fundamentalist Islamic followers of Nursi (1876-1960) to show the interaction between religion and society. He follows parallel development in such fields as the world communications revolution, political and social reform, intellectual development and religious history. Paper edition (unseen), $16.95. Annotation copyrighted by Book News, Inc., Portland, OR.
Includes bibliographical references (pages 233-251) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Nursi, Said, -- 1873-1960 -- Philosophy; Nursi, Said, -- 1873-1960; Nurculuk; Islam -- Turkey -- History; Islamic sociology; Islam; Social change; Islam; Social Change; Religious Philosophies; Turkey; Nurcu; Islam; Sociologie religieuse -- Islam; Changement social; Islam; SOCIAL SCIENCE -- Sociology of Religion; Social change; Islam; Islamic sociology; Nurculuk; Philosophy; Turkey; History